2020
DOI: 10.1186/s12862-020-01648-x
|View full text |Cite
|
Sign up to set email alerts
|

Ecomorphological divergence and habitat lability in the context of robust patterns of modularity in the cichlid feeding apparatus

Abstract: Background: Adaptive radiations are characterized by extreme and/or iterative phenotypic divergence; however, such variation does not accumulate evenly across an organism. Instead, it is often partitioned into sub-units, or modules, which can differentially respond to selection. While it is recognized that changing the pattern of modularity or the strength of covariation (integration) can influence the range or rate of morphological evolution, the relationship between shape variation and covariation remains un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 89 publications
1
24
0
Order By: Relevance
“…While a worthy consideration, we do not believe it represents a major confounding factor here. For one, we have found that, while differences exist (Parsons et al 2012), patterns of modularity and levels of integration are highly conserved across cichlids (Parsons et al 2011b;Conith et al 2020), and lines of zebrafish (Parsons et al 2018). Further, Lake Malawi cichlid species are continuing to sort alleles due to hybridization in the wild (Svardal et al 2020), meaning that hybrid populations represent a "natural" state in the lake.…”
Section: Plasticity Is Correlated Across Anatomical Units: Function Vmentioning
confidence: 99%
“…While a worthy consideration, we do not believe it represents a major confounding factor here. For one, we have found that, while differences exist (Parsons et al 2012), patterns of modularity and levels of integration are highly conserved across cichlids (Parsons et al 2011b;Conith et al 2020), and lines of zebrafish (Parsons et al 2018). Further, Lake Malawi cichlid species are continuing to sort alleles due to hybridization in the wild (Svardal et al 2020), meaning that hybrid populations represent a "natural" state in the lake.…”
Section: Plasticity Is Correlated Across Anatomical Units: Function Vmentioning
confidence: 99%
“…Most unique tissues that express lg in the MH lineage are well known to be related to adaptation. For example, the hatching gland is a key innovation in regulating the hatching period of aquatic embryos to become free-living larvae 32 ; the pharyngeal cartilages related to feeding and ecological niche exploration are key to cichlid fishes adaptive radiation [33][34][35] ; epidermal serotonergic neuroepithelial cells are chemoreceptors related to environmental stimuli such as hypoxia 36 ; and the olfactory epithelium is famous for the detection of odorants, such as amino acids, hormones and pheromones 37 . lg is also highly expressed in the heart valves, a key innovation to control unidirectional blood flow 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, lg evolved new regulatory functions in cichlid fishes, especially in its most species-richness lineage, the MH lineage. For example, in the hatching gland which is a key innovation to regulate the hatching period of embryos to become free-living larvaes 29 ; in pharyngeal cartilages, the well-known tissues related to feeding and ecological niche exploration, are key to cichlid fish adaptive radiation 3032 ; in scattered epidermal serotonin-positive cells which are neuroepithelia cells related to environmental stimuli, such as water flow, pheromone and hormone 33,34 ; in the olfactory epithelium which is well-known for detection of odorants, such as amino acid, hormone and pheromone 35 . Considering that some of these tissues are derived from a key vertebrate innovation, the neural crest cells 36 , lg can be also causally linked to neural crest cell development and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this evidence, and other previously published trees of Tropheops (i.e. Conith et al, 2020a , b ), we substituted the trait values of Tropheops sp . ‘red cheek’ and Tropheops sp .…”
Section: Methodsmentioning
confidence: 99%